2011
DOI: 10.1074/jbc.m110.177451
|View full text |Cite
|
Sign up to set email alerts
|

New Regulators of a High Affinity Ca2+ Influx System Revealed through a Genome-wide Screen in Yeast

Abstract: The bakers' yeast Saccharomyces cerevisiae utilizes a high affinity Ca 2؉ influx system (HACS) to survive assaults by mating pheromones, tunicamycin, and azole-class antifungal agents. HACS consists of two known subunits, Cch1 and Mid1, that are homologous and analogous to the catalytic ␣-subunits and regulatory ␣2␦-subunits of mammalian voltage-gated calcium channels, respectively. To search for additional subunits and regulators of HACS, a collection of gene knock-out mutants was screened for abnormal uptake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
100
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(106 citation statements)
references
References 58 publications
(33 reference statements)
5
100
1
Order By: Relevance
“…Calcineurin then dephosphorylates the transcription factor Crz1, resulting in the translocation of Crz1 from cytoplasm to nucleus and consequent activation of expression of CDRE genes, such as CCH1, PMR1 and PMC1 (Karababa et al, 2006;Cronin et al, 2002). Moreover, calcineurin appears to inhibit calcium influx via a feedback loop by dephosphorylating Cch1, whose phosphorylation is essential for its activity (Bonilla & Cunningham, 2003;Martin, et al, 2011). This calcium signalling pathway, termed the cell calcium survival pathway, is required for tolerance to ergosterol biosynthesis inhibitors, survival of calcium depletion and other responses to ER stresses (Bonilla & Cunningham, 2003;Onyewu et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Calcineurin then dephosphorylates the transcription factor Crz1, resulting in the translocation of Crz1 from cytoplasm to nucleus and consequent activation of expression of CDRE genes, such as CCH1, PMR1 and PMC1 (Karababa et al, 2006;Cronin et al, 2002). Moreover, calcineurin appears to inhibit calcium influx via a feedback loop by dephosphorylating Cch1, whose phosphorylation is essential for its activity (Bonilla & Cunningham, 2003;Martin, et al, 2011). This calcium signalling pathway, termed the cell calcium survival pathway, is required for tolerance to ergosterol biosynthesis inhibitors, survival of calcium depletion and other responses to ER stresses (Bonilla & Cunningham, 2003;Onyewu et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Together, these three proteins form a high-affinity Ca 2+ system (HACS) that can cause an influx of Ca 2+ across the plasma membrane. Although Cch1p shows significant sequence and structural homology to VGCCs, Ca 2+ movement through Cch1p is not voltage dependent (Martin et al, 2011). Studies on Cch1p have revealed that it responds to different stimuli that include a sudden increase in pH (Viladevall et al, 2004), exposure to mating pheromones (Iida et al, 1994;Muller et al, 2001), store-operated stress (D'hooge et al, 2015;Locke et al, 2000), endoplasmic reticulum (ER) stress (Hong et al, 2010;Locke et al, 2000) and oxidative stress (Popa et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Like the mammalian voltage-gated Ca 2+ channel α 1 subunit (known as CACNA1C), the Cch1p protein contains four structurally similar domains (I-IV), with each domain having six transmembrane domain (TMD) segments (Martin et al, 2011;Paidhungat and Garrett, 1997). To be functional, Cch1p needs another plasma membrane protein, Mid1p, which is broadly conserved in yeast and fungi and has been recently reported to resemble the mammalian α and δ subunit because of its structural features (Iida et al, 1994;Martin et al, 2011). Ecm7p, the third component of the Cch1p complex is related to the γ subunit of VGCCs and is a member of the claudin superfamily (Martin et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, HACS activity likely involves calcineurin-dependent activation of Ste12p (Muller et al, 2001). The work by Martin et al (2011) indicates that, depending on the nature of the stimulus, HACS regulation may or may not involve calcineurin action. For example, calcium influx after high pH shock is calcineurin independent.…”
Section: Cation Flows Across Cellular Membranes Ion Channelsmentioning
confidence: 99%